An investigation of Teachers' Attitudes towards Low academic achievers: A perspective of Diagnostic Remedial Teaching at Federal Government Educational Institutions - Sheer, Muhammad; Ullah, Fawad; Hakeem, Luqman (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Quality teaching methods such as Diagnostic Remedial Teaching (DRT) and the positive attitude of teachers significantly enhance the academic achievement of the students. This study investigates whether traditional teaching methods and negative attitudes of teachers play any significant role in the poor performance of low academic achievements. The study's objectives were to determine teachers' attitudes toward low academic achievers, Diagnostic Remedial Teaching (DRT), and the problems involved in implementing DRT in the classrooms. The sample size covers 42 Federal Government Educational Institutes (FGEI) in Khyber Pakhtunkhwa, Pakistan, involving 230 teachers and 22 principals. Findings reveal that the teachers hold a positive attitude toward implementing Diagnostic Remedial teaching (DRT) in the classroom. Still, inadequate training and heavy workloads of the teachers were the primary challenges. In addition, their attitudes toward low academic achievers were positive. However, they held negative attitudes towards those students who enrolled in the institutes without qualifying for the admission test standard criteria.